Stiff Person Syndrome: A Rare Neurological Disorder, Heterogeneous in Clinical Presentation and Not Easy to Treat - Susanne Buechner; Igor Florio; Loredana Capone (Case Reports in Neurological Medicine)
Background. Stiff person syndrome (SPS) is a rare neurological disorder characterized by progressive rigidity of axial and limb muscles associated with painful spasms. SPS can be classified into classic SPS, paraneoplastic SPS, and SPS variants. Its underlying pathogenesis is probably autoimmune, as in most cases antibodies against glutamic acid decarboxylase (GAD) are observed. Similarly, paraneoplastic SPS is usually linked to anti-amphiphysin antibodies. Treatment is based on drugs enhancing gamma-aminobutyric acid (GABA) transmission and immunomodulatory agents. Case Series. Patient 1 is a 45-year-old male affected by the classic SPS, Patient 2 is a 73-year-old male affected by paraneoplastic SPS, and Patient 3 is a 68-year-old male affected by the stiff limb syndrome, a SPS variant where symptoms are confined to the limbs. Symptoms, diagnostic findings, and clinical course were extremely variable in the three patients, and treatment was often unsatisfactory and not well tolerated, thus reducing patient compliance. Clinical manifestations also included some unusual features such as recurrent vomiting and progressive dysarthria. Conclusions. SPS is a rare disorder that causes significant disability. Because of its extensive clinical variability, a multitask and personalized treatment is indicated. A clearer understanding of uncommon clinical features and better-tolerated therapeutic strategies are still needed.